Thermal insulation concrete material and preparation method thereof

By using specific components and expanded ore powder in concrete materials, the problem of insufficient strength and toughness of thermal insulation concrete materials in the prior art is solved, and better thermal insulation and mechanical properties are achieved, and the building is extended. The lifespan of the object and simplifies the preparation process.

CN119430812APending Publication Date: 2025-02-14CHINA CONSTR WEST CONSTR SOUTHWEST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411820678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing thermal insulation concrete materials cannot take into account both thermal insulation, strength and toughness, and the preparation process is complicated.

Method used

Using concrete material formulas including silicate cement, walnut sand, ceramic sand, fly ash and expanded ore powder, the highly absorbent resin of expanded ore powder, montmorillonite powder, polyacrylate and polyacrylamide Such raw materials improve the dispersion and gelation reaction of concrete, increase crack-resistant fibers to improve toughness and strength.

Benefits of technology

It significantly improves the insulation performance, mechanical properties, permeability, temperature adaptability and impact resistance of concrete, extends the service life of the building, simplifies the preparation method, and reduces the cost of raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183031560000061
    Figure BDA0005183031560000061
  • Figure BDA0005183031560000071
    Figure BDA0005183031560000071
Patent Text Reader

Abstract

The invention discloses a thermal insulation concrete material and a preparation method thereof, and the thermal insulation concrete material comprises the following components by weight: 30-40 parts of Portland cement, 5-10 parts of quartz sand, 5-10 parts of walnut sand, 5-10 parts of ceramsite sand, 5-10 parts of redispersible latex powder, 10-15 parts of fly ash, 20-30 parts of water, 1-2 parts of polyvinyl alcohol, 1-2 parts of polyacrylamide, 1-3 parts of hydroxypropyl methyl cellulose ether, and 1-3 parts of modified polyoxyethylene. 1-2 parts of anti-crack fibers, 2-4 parts of a water reducing agent and 2-4 parts of expanded mineral powder; the expanded mineral powder is prepared from the following raw materials: water-absorbent resin, montmorillonite powder, polyacrylate and polyacrylamide. The concrete material disclosed by the invention has better heat insulation performance, the toughness and the strength are effectively improved, and the concrete material is prevented from cracking and generating cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a heat insulating concrete material and a preparation method thereof. Background Art

[0002] Buildings are exposed to the erosion of wind and sun for a long time. Using good exterior walls can extend the service life of the building. At least 30% of the energy for heating in winter and cooling in summer is lost through doors, windows and walls every year, which requires the thermal insulation performance of the building envelope structure.

[0003] By adding an insulation layer made of insulation materials to the exterior wall, the insulation effect of the exterior wall can be effectively improved. At present, the commonly used insulation materials are mainly made of polystyrene board materials. However, although the existing thermal insulation exterior wall materials have a certain insulation capacity, their strength and toughness are low. Under environmental conditions with a large temperature difference between day and night, they are prone to cracking and falling off, and cannot effectively guarantee the service life of the building.

[0004] In the prior art, patent CN111825391A discloses a lightweight high-strength self-insulating concrete for prefabricated buildings, wherein the components are as follows by mass percentage: 45-8% cementitious material, 6-9% modified fly ash floating beads, 12-18% high-strength low-density plastic, 20-25% aerogel ceramic sand, 0.8-1.2% polycarboxylic acid water reducer, and 9-11% water; the prepared concrete has high strength, light weight, and good thermal insulation, but its preparation method is relatively complicated and needs further improvement.

[0005] Patent CN114230280A discloses a high-insulation lightweight high-strength concrete and its preparation method, which consists of the following components by weight: 20-35% cement, 30-45% ceramsite, 15-25% vitrified microspheres, 3-5% Miscanthus fiber, 0.5-1.5% water reducer, 0.8-1.5% foaming agent, 8-15% water; it has the advantages of low raw material cost, simple preparation method, and high insulation. However, the strength of the obtained lightweight insulation concrete is limited and it is difficult to meet the construction requirements.

[0006] Patent CN108726944A discloses a high-strength concrete with thermal insulation function and its preparation method, which uses the following raw materials by weight: 32-36 parts of ordinary Portland cement, 24-28 parts of sand, 13-16 parts of tailings sand, 12-16 parts of banana fiber / aliphatic epoxy resin, 8-14 parts of nano-alumina dispersion saturated liquid modified modal fiber, 3-5 parts of lignin, 2-4 parts of expanded chlorite powder, and 1-3 parts of expanded graphite to prepare high-strength concrete with good thermal insulation performance. However, the source of its raw materials is limited, which is not conducive to promotion and application and cost reduction.

[0007] In view of this, this patent application is filed. Summary of the invention

[0008] In order to solve the technical problems that the existing thermal insulation concrete materials cannot take into account thermal insulation, strength, insufficient toughness and complex preparation process, the present invention provides a thermal insulation concrete material, which effectively improves the toughness and strength of the concrete material while providing better thermal insulation effect, and prevents the concrete material from cracking and fissures.

[0009] The first object of the present invention is to provide a heat-insulating concrete material, comprising the following components in parts by weight: 30-40 parts of silicate cement, 5-10 parts of quartz sand, 5-10 parts of walnut sand, 5-10 parts of ceramsite sand, 5-10 parts of redispersible latex powder, 10-15 parts of fly ash, 20-30 parts of water, 1-2 parts of polyvinyl alcohol, 1-2 parts of polyacrylamide, 1-3 parts of hydroxypropyl methyl cellulose ether, 1-3 parts of modified polyethylene oxide, 1-2 parts of anti-cracking fiber, 2-4 parts of water reducer, and 2-4 parts of expanded mineral powder;

[0010] The raw materials for preparing the expanded mineral powder include water-absorbent resin, montmorillonite powder, polyacrylic acid salt and polyacrylamide.

[0011] The present invention rationally designs the components of concrete materials, adds expanded mineral powder into the concrete materials, and uses highly absorbent resin, montmorillonite powder, polyacrylic acid salt and polyacrylamide as main raw materials of the expanded mineral powder. Through the surface activity of polyacrylic acid salt, the hydrophobic base end is directionally adsorbed on the surface of cement particles, thereby increasing the electrostatic repulsion between cement particles and making the cement particles disperse more evenly. The addition of montmorillonite powder just fills the space between cement particles and increases the adsorption force, thereby better affinity with water and water reducing agent and plays a lubricating role. The absorbent resin can better bond the two together, thereby making the glue suspension liquid coagulate better. The addition of polyacrylamide further improves the working performance of concrete, improves the compression resistance, flexural resistance, bending toughness and expansion of concrete, and reduces the permeability and shrinkage. Therefore, the expanded mineral powder can well fill the capillary pores of concrete, improve the pore structure, increase the coagulation speed of cementitious materials during the hydration process, accelerate the hydration process of cementitious materials, improve the density, impermeability, flexibility and compressive strength of concrete, and have a good effect on improving the compression and crack resistance of the material; at the same time, the expanded mineral powder in the present invention can also produce appropriate expansion during the mixing of concrete, giving the concrete foundation thermal insulation performance.

[0012] The walnut sand and ceramsite sand added in the present invention can reduce the thermal conductivity of concrete while adjusting the concrete bulk density, ensuring good thermal insulation performance of concrete. The anti-cracking fiber can make the internal stress distribution of concrete more uniform, thereby improving the toughness and strength of concrete, and giving the concrete exterior wall a part of the load-bearing function. At the same time, the anti-cracking fiber is added to the concrete and is evenly distributed in all directions. It can be closely combined with the cementitious material, the hydration reaction of the cementitious material is more thorough, the aggregate segregation is reduced, and the gradation is more uniform, thereby alleviating the effect of the internal stress of the concrete caused by temperature changes, so that the concrete can better adapt to temperature differences, and improve the concrete's impermeability, frost resistance, and impact resistance.

[0013] The concrete material formula of the present invention significantly improves the thermal insulation performance, mechanical properties, impermeability, temperature adaptability, impact resistance, etc. of the concrete. The concrete can be used to build high-quality thermal insulation exterior walls, and its good strength and toughness will significantly extend the life of the building.

[0014] As a preferred design, the mass proportions of the raw materials in the expanded mineral powder are: 5 to 10 parts of water-absorbent resin, 55 to 65 parts of montmorillonite powder, 20 to 30 parts of polyacrylic acid salt, and 2 to 6 parts of polyacrylamide.

[0015] As a preferred design, the water absorption rate of the water-absorbent resin is 600 to 800 times.

[0016] As a preferred design, the particle size of the montmorillonite powder is 200-325 mesh, and the apparent density is 4-6 g / cm 3 , the expansion multiple is 30 to 40 times.

[0017] As a preferred design, the fineness modulus of the quartz sand is 2.6 to 3.3;

[0018] And / or, the particle size of the walnut sand is 0.6 to 1.18 mm;

[0019] And / or, the particle size of the ceramsite sand is 2 to 6 mm.

[0020] As a preferred design, the redispersible latex powder is a vinyl acetate / versatate copolymer or an ethylene / vinyl acetate copolymer.

[0021] As a preferred design, the anti-cracking fiber is any one of polypropylene fiber and polyvinyl alcohol fiber;

[0022] and / or the length of the anti-cracking fiber is 3 to 20 mm and the diameter is 15 to 48 um;

[0023] And / or the elastic modulus of the crack-resistant fiber is 3500-4000 MPa.

[0024] As a preferred design, when the modified polyethylene oxide has a solution viscosity of 0.5%, its pH value is 7-9. For example, QX5596 / H and QX5597 / H can be used.

[0025] As a preferred design, the water reducer is any one of a polycarboxylic acid water reducer and a fatty acid water reducer.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The thermal insulation concrete material provided by the present invention has better thermal insulation performance, effectively improves the toughness and strength of the concrete material, and prevents the concrete material from cracking and forming cracks.

[0028] Specifically:

[0029] The present invention uses ordinary Portland cement, walnut sand, ceramsite sand and fly ash as main materials. The expansion mineral powder is added to store a part of water in the early stage of concrete hydration, thereby reducing the hydration heat of concrete and reducing the risk of concrete cracking; at the same time, the cement particles are evenly dispersed, and water is slowly released in the later stage to promote the hydration of cementitious materials, so that the capillary filling of concrete is more dense, the self-shrinkage of concrete is reduced, and the compressive strength, impermeability and bending toughness of concrete are improved; at the same time, appropriate expansion is generated during the mixing of concrete, so as to further improve the thermal insulation performance of concrete.

[0030] The addition of polyvinyl alcohol, polyacrylamide, hydroxypropyl methyl cellulose ether and modified polyethylene oxide can effectively improve the construction performance of concrete, increase the lubricity between hydrated molecules, make the cementitious material wrap fine aggregate more evenly, and improve the thermal insulation effect of concrete.

[0031] The addition of anti-crack fiber further cleverly solves the problem of cracks that are prone to occur when the exterior wall area is large. Relying on its unique tensile strength, dispersibility, melting point, acid and alkali resistance and other properties, it can effectively reduce aggregate segregation, increase the toughness and strength of concrete, and prevent the generation and development of concrete cracks.

[0032] (2) In the present invention, the formula of the concrete material is cleverly designed, the preparation method is simplified, the operation is simple, and the raw material liquid is easily available, which is conducive to popularization and application and cost reduction. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0034] In the following examples, "parts" used represent parts by mass.

[0035] The silicate cement is ordinary silicate cement with a strength grade of P.O42.5R and a specific surface area of ​​360m 2 / kg.

[0036] The quartz sand has a fineness modulus of 2.8, the walnut sand has a particle size of 0.6-1.18 mm, and the ceramsite sand has a particle size of 2-6 mm.

[0037] The fly ash is of grade II and has a specific surface area of ​​350m 2 / kg, activity index 75%.

[0038] The redispersible latex powder is Ethylene / Vinyl acetate of Copolymer The manufacturer is Langfang Tianya Energy Saving Technology Co., Ltd., the solid content is 98wt%, and the bulk density is 400g / l.

[0039] The molecular weight of the polyvinyl alcohol is 120,000, the molecular weight of the polyacrylamide is 13 million, the molecular weight of the hydroxypropyl methylcellulose ether is 100,000, and the modified polyethylene oxide is QX5596 / H produced by Shanghai Yingjia Industrial Development Co., Ltd.

[0040] The anti-cracking fiber is a polypropylene fiber with a length of 3 to 20 mm, a diameter of 15 to 48 μm, and an elastic modulus of 3500 MPa.

[0041] The water reducing agent is a polycarboxylic acid high-performance water reducing agent: solid content 25%, water reduction rate 27%.

[0042] The expanded mineral powder is composed of 6 parts of super absorbent resin (particle size 40 mesh, water absorption rate 700 times), montmorillonite powder (particle size 200 mesh, apparent density 5g / cm 3 ) 65 parts, polyacrylic acid salt (molecular weight 1000) 25 parts, polyacrylamide (molecular weight 13 million) 4 parts;

[0043] The specific preparation method of expanded mineral powder is as follows:

[0044] 1) Weigh 65 parts of montmorillonite powder and 25 parts of polyacrylate in a container, stir and mix evenly to obtain a uniformly dispersed montmorillonite mixture;

[0045] 2) Weigh 6 parts of highly absorbent resin and 4 parts of polyacrylamide and add them to the montmorillonite mixture, and continue stirring for 1.5 hours to obtain expanded mineral powder.

[0046] Example 1

[0047] A heat-insulating concrete material, the raw materials of which are measured by weight: 30 parts of silicate cement, 5 parts of quartz sand, 5 parts of walnut sand, 10 parts of ceramsite sand, 10 parts of redispersible latex powder, 10 parts of fly ash, 20 parts of water, 1 part of polyvinyl alcohol, 1 part of polyacrylamide, 1 part of hydroxypropyl methyl cellulose ether, 1 part of modified polyethylene oxide, 1 part of anti-cracking fiber, 2 parts of water reducing agent, and 3 parts of expanded mineral powder;

[0048] 2) adding the weighed silicate cement, quartz sand, walnut sand, ceramsite sand, redispersible latex powder and fly ash into a concrete mixer and stirring for 10 hours to obtain a mixture; then weighing polyvinyl alcohol, polyacrylamide, hydroxypropyl methyl cellulose ether, modified polyethylene oxide, anti-cracking fiber, water reducer, expansion mineral powder and water in the formula, adding them to the mixture, and turning on the mixer again until stirring is uniform, thereby completing the preparation of thermal insulation concrete.

[0049] Example 2

[0050] A thermal insulation concrete material, the preparation method of which is roughly the same as that of Example 1, and the raw materials thereof are measured by weight: 35 parts of silicate cement, 5 parts of quartz sand, 10 parts of walnut sand, 5 parts of ceramsite sand, 5 parts of redispersible latex powder, 10 parts of fly ash, 20 parts of water, 1 part of polyvinyl alcohol, 1 part of polyacrylamide, 2 parts of hydroxypropyl methylcellulose ether, 1 part of modified polyethylene oxide, 1 part of anti-cracking fiber, 2 parts of water reducer, and 2 parts of expanded mineral powder.

[0051] Example 3

[0052] A thermal insulation concrete material, the preparation method of which is roughly the same as that of Example 1, and the raw materials thereof are measured by weight: 40 parts of silicate cement, 5 parts of quartz sand, 5 parts of walnut sand, 5 parts of ceramsite sand, 5 parts of redispersible latex powder, 10 parts of fly ash, 20 parts of water, 2 parts of polyvinyl alcohol, 1 part of polyacrylamide, 1 part of hydroxypropyl methyl cellulose ether, 1 part of modified polyethylene oxide, 1 part of anti-cracking fiber, 2 parts of water reducer, and 2 parts of expanded mineral powder.

[0053] Comparative Example 1

[0054] A heat insulating concrete material, the preparation method of which is substantially the same as that of Example 1, and the raw materials thereof are the same as those of the example in terms of weight.

[0055] The difference from Example 1 is the components of the expanded mineral powder, and its preparation method is roughly the same as the above-mentioned implementation method, and its raw materials and their weight proportions are: 65 parts of montmorillonite powder, 30 parts of polyacrylic acid salt, and 5 parts of polyacrylamide. No super absorbent resin is added.

[0056] Comparative Example 2

[0057] A heat insulating concrete material, the preparation method of which is substantially the same as that of Example 1, and the raw materials thereof are the same as those of the example in terms of weight.

[0058] The difference from Example 1 is the composition of the expanded mineral powder. Its preparation method is roughly the same as the above-mentioned implementation method. Its raw materials and their weight proportions are: 10 parts of water-absorbent resin, 50 parts of montmorillonite powder, 35 parts of polyacrylic acid salt, and 5 parts of polyacrylamide.

[0059] Comparative Example 3

[0060] A heat insulating concrete material, the preparation method of which is substantially the same as that of Example 1, and the raw materials thereof are the same as those of the example in terms of weight.

[0061] The difference between it and Example 1 is the components of the expanded mineral powder. Its preparation method is roughly the same as the above-mentioned implementation method. Its raw materials and their weight proportions are: 10 parts of water-absorbent resin, 70 parts of montmorillonite powder, 15 parts of polyacrylic acid salt, and 5 parts of polyacrylamide.

[0062] Comparative Example 4

[0063] A heat insulating concrete material, the preparation method of which is substantially the same as that of Example 1, and the raw materials thereof are the same as those of the example in terms of weight.

[0064] The difference between it and Example 1 lies in the components of the expanded mineral powder. Its preparation method is roughly the same as the above-mentioned implementation method. Its raw materials and their weight proportions are: 10 parts of water-absorbent resin, 65 parts of montmorillonite powder, 25 parts of polyacrylic acid salt, and no polyacrylamide is added.

[0065] Comparative Example 5

[0066] A heat insulating concrete material, the preparation method of which is substantially the same as that of Example 1, and the raw materials thereof are the same as those of the example in terms of weight.

[0067] The difference between it and Example 1 lies in the components of the expanded mineral powder. Its preparation method is roughly the same as the above-mentioned implementation method. Its raw materials and their weight proportions are: 10 parts of water-absorbent resin, 60 parts of montmorillonite powder, 20 parts of polyacrylic acid salt, and 10 parts of polyacrylamide.

[0068] Comparative Example 6

[0069] A heat-insulating concrete material, without the addition of expansion mineral powder, is prepared in the same manner as in Example 1, and the raw materials are weighed in parts by weight: 30 parts of silicate cement, 5 parts of quartz sand, 5 parts of walnut sand, 10 parts of ceramsite sand, 10 parts of redispersible latex powder, 13 parts of fly ash, 20 parts of water, 1 part of polyvinyl alcohol, 1 part of polyacrylamide, 1 part of hydroxypropyl methylcellulose ether, 1 part of modified polyethylene oxide, 1 part of anti-cracking fiber, and 2 parts of water reducer. No expansion mineral powder is added in this comparative example.

[0070] Comparative Example 7

[0071] A heat-insulating concrete material, the preparation method of which is substantially the same as that of Example 1, except that the addition of walnut sand is removed, and the raw materials are calculated by weight: 30 parts of silicate cement, 10 parts of quartz sand, 10 parts of ceramsite sand, 10 parts of redispersible latex powder, 10 parts of fly ash, 20 parts of water, 1 part of polyvinyl alcohol, 1 part of polyacrylamide, 1 part of hydroxypropyl methylcellulose ether, 1 part of modified polyethylene oxide, 1 part of anti-cracking fiber, 2 parts of water reducer, and 3 parts of expanded mineral powder.

[0072] Comparative Example 8

[0073] A heat-insulating concrete material, the preparation method of which is substantially the same as that of Example 1, except that the addition of anti-cracking fiber is removed, and the raw materials are calculated by weight: 30 parts of silicate cement, 5 parts of quartz sand, 5 parts of walnut sand, 10 parts of ceramsite sand, 10 parts of redispersible latex powder, 10 parts of fly ash, 20 parts of water, 1 part of polyvinyl alcohol, 1 part of polyacrylamide, 1 part of hydroxypropyl methylcellulose ether, 1 part of modified polyethylene oxide, 2 parts of water reducer, and 4 parts of expanded mineral powder.

[0074] Performance Test:

[0075] The thermal conductivity of each group of concrete in Examples 1 to 3 and Comparative Examples 1 to 8 was tested by a thermal conductivity tester (TSWL-DR3030); the compressive strength of each group of concrete in Examples 1 to 3 and Comparative Examples 1 to 8 was tested by a pressure tester; the tensile strength of each group of concrete in Examples 1 to 3 and Comparative Examples 1 to 8 was tested by a tensile tester; the thermal conductivity, compressive strength and tensile strength of each group of concrete were used to reflect its thermal insulation performance, mechanical properties and toughness respectively, and ordinary concrete with a strength grade of C20 was designed as a reference group. The thermal conductivity, 28d compressive strength and tensile strength of each group of concrete are shown in Table 1 below.

[0076] Table 1 Thermal insulation properties and mechanical properties of concrete in each group

[0077]

[0078]

[0079] As can be seen from Table 1, compared with the C20 ordinary concrete of the benchmark group, the thermal conductivity of the concrete in Examples 1 to 3 is greatly reduced, all within 0.2 W·(m·K). ~1The thermal insulation performance is significantly improved; and the 28d compressive strength and flexural strength of the concrete in Examples 1 to 3 are significantly increased, and the mechanical properties are good; at the same time, the 28d compressive strength of the concrete in Examples 1 to 3 is increased by multiples, the bending toughness of the concrete is enhanced, the ability to resist tensile stress is strong, and the crack resistance is good. The average thermal conductivity of the concrete in Comparative Examples 1 to 6 is increased to 0.6W·(m·K) ~1 The thermal conductivity of the concrete increased by more than 200% compared with that of Example 1, and the thermal insulation performance decreased significantly. At the same time, the compressive strength, flexural strength and tensile strength decreased significantly. According to the proportion, the concrete performance changed significantly by changing the proportion of the expanding mineral powder or not adding the expanding mineral powder, especially the thermal conductivity of the concrete, which shows that the expanding mineral powder has a particularly obvious effect on the thermal insulation performance of the concrete, and the components in the expanding mineral powder affect each other.

[0080] Compared with Example 1, the thermal conductivity of Comparative Example 7 is 0.453 W·(m·K) ~1 It is obviously larger, the thermal insulation performance is weaker, and other mechanical properties are almost unaffected, indicating that walnut sand replaces part of the quartz sand, has a stronger adaptability to the wrapping of the adhesive, a slower evaporation rate, a stronger water retention capacity, and a more uniform distribution. Under the interaction of internal stresses in the porous walnut sand, the thermal insulation performance of the concrete is better.

[0081] Compared with Example 1, in Comparative Example 8, the thermal insulation performance of concrete is significantly improved, the tensile strength is low, the compressive strength is almost unchanged, and the thermal insulation performance is improved by more than the tensile strength is reduced. This shows that the expanded mineral powder mainly affects the thermal insulation performance of concrete, and the anti-cracking fiber mainly affects the bending toughness of concrete.

[0082] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A thermal insulation concrete material, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of silicate cement, 5-10 parts of quartz sand, 5-10 parts of walnut sand, 5-10 parts of ceramsite sand, 5-10 parts of redispersible latex powder, 10-15 parts of fly ash, 20-30 parts of water, 1-2 parts of polyvinyl alcohol, 1-2 parts of polyacrylamide, 1-3 parts of hydroxypropyl methyl cellulose ether, 1-3 parts of modified polyethylene oxide, 1-2 parts of anti-cracking fiber, 2-4 parts of water reducing agent and 2-4 parts of expanded mineral powder; The raw materials for preparing the expanded mineral powder include water-absorbent resin, montmorillonite powder, polyacrylic acid salt and polyacrylamide.

2. A thermal insulation concrete material according to claim 1, characterized in that: The weight proportions of the raw materials in the expanded mineral powder are: 5-10 parts of water-absorbing resin, 55-65 parts of montmorillonite powder, 20-30 parts of polyacrylic acid salt, and 2-6 parts of polyacrylamide.

3. A thermal insulation concrete material according to claim 1 or 2, characterized in that: The water absorption rate of the water-absorbent resin is 600 to 800 times.

4. A thermal insulation concrete material according to claim 1 or 2, characterized in that: The particle size of the montmorillonite powder is 200-325 mesh, and the apparent density is 4-6 g / cm 3 , the expansion multiple is 30 to 40 times.

5. The heat insulating concrete material according to claim 1, characterized in that: The fineness modulus of the quartz sand is 2.6 to 3.3; And / or, the particle size of the walnut sand is 0.6 to 1.18 mm; And / or, the particle size of the ceramsite sand is 2 to 6 mm.

6. The heat insulating concrete material according to claim 1, characterized in that: The redispersible latex powder is a vinyl acetate / versatate vinyl copolymer or Ethylene / Vinyl acetate of Copolymer .

7. The heat insulating concrete material according to claim 1, characterized in that: The anti-cracking fiber is any one of polypropylene fiber and polyvinyl alcohol fiber; and / or the length of the anti-cracking fiber is 3 to 20 mm and the diameter is 15 to 48 um; And / or the elastic modulus of the crack-resistant fiber is 3500-4000 MPa.

8. The heat insulating concrete material according to claim 1, characterized in that: When the modified polyethylene oxide has a solution viscosity of 0.5%, the pH value thereof is 7-9.

9. The heat insulating concrete material according to claim 1, characterized in that: The water reducer is any one of a polycarboxylic acid water reducer and a fatty acid water reducer.

10. The method for preparing a heat insulating concrete material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Add silicate cement, quartz sand, walnut sand, ceramsite sand, redispersible latex powder and fly ash weighed according to the proportion into a concrete mixer and stir for 8 to 15 hours to obtain a mixture; 2) adding the weighed polyvinyl alcohol, polyacrylamide, hydroxypropyl methylcellulose ether, modified polyethylene oxide, anti-cracking fiber, water reducer, expansion mineral powder and water into the mixture, and starting the mixer again until the mixture is uniformly stirred to obtain heat insulating concrete.

Citation Information

Patent Citations

  • High-strength concrete with heat preservation and insulation functions and preparation method of high-strength concrete with heat preservation and insulation functions

    CN108726944A

  • Light high-strength self-thermal insulation concrete for fabricated building

    CN111825391A